PENGARUH LABEL HALAL, PERFORMANCE, CONFORMANCE DAN FEATURES TERHADAP KEPUTUSAN PEMBELIAN KERIPIK TEMPE HAIBEE CHIPS - Rohmatika, Bela; Hastuti, Dewi; Subekti, Endah; Prabowo, Rossi (Universitas Mathla’ul Anwar Banten, 2024)
The aim of the research is to determine the influence of the Halal Label, Performance, Conformance and Features on the decision to purchase Haibee Chips tempe chips. The basic method of this research is a combination method, while the sample was taken by accidental sampling as many as 75 consumers. The analysis method uses multiple linear regression analysis. The research results show that descriptively the variable data for halal labels is 92 (strongly agree), conformance 80 (agree), features 78 (agree) and performance 78 (agree). Based on regression analysis together with the F Test, the halal label, performance, conformance and features variables have a significant effect on purchasing decisions at α 0.000 < 0.01 (1%). Partially in the T test, the variables that influence the decision to purchase Haibee Chips tempeh chips are the halal label variable 0.040 < 0.05, conformance 0.000 < 0.01, features 0.000 < 0.01. And the variable that has no real influence is performance 0.324 > 0.05. The conclusion is that purchasing decisions are influenced by the halal label, conformance, features and performance.